Maintain Body Fitness in the pandemic with video tutorials Senam Cegah Covid19 (SCC19) with Nusantara Aerobic Nusantara University PGRI Kediri in 2020 - Puspodari; Moh. Nur Kholis; Septyaning Lusianti; Setyo Harmono; Dhedy Yuliawan; Yanuar Rizky (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
Sport is a form of physical activity that is carried out in a planned and structured manner which in its implementation involves repetitive body movements to improve physical and spiritual fitness. Sport becomes an important thing and must be done by the community in the midst of a COVID-19 pandemic. Because sports activities can improve fitness and increase endurance so it can be ensured that immunity becomes strong as a defense against the virus that causes COVID-19. Conducting Physical Distancing is an appeal by the World Health Organization (WHO) which has changed the way we live everyday. Began to do the teaching and learning process, work, worship also exercise at home. When doing physical exercise it is recommended not to overdo it with high intensity. Because, it can interfere with health. Prevent Covid-19 (SCC-19) is a type of exercise that is intended to prevent covid-19 to improve fitness and endurance. SCC is expected to be an alternative way to maintain health, fitness and endurance. This activity was carried out by conducting a virtual demonstration with a video tutorial on the movement of the gymnastics created by SCC-19, which was exhibited by the Nusantara Aerobic team, Nusantara University PGRI Kediri. The target subjects of this activity are all sports activists. The results of this activity indicate that there is good enthusiasm from the total audience of 4,625.